Influence of screw to joint distance on articular subsidence in tibial‐plateau fractures. Issue 4 (12th February 2019) - Ye, Xuan; Huang, Dawei; Perriman, Diana M.; Smith, Paul N.
Abstract : Background: Tibial‐plateau fractures with depressed osteochondral fragments have a high incidence of articular subsidence post reduction. Locking plates aim to prevent this via 'raft' screws below the subchondral bone. However, differences in plate design and patient anatomy result in variability of screw position in relation to the fragments they are designed to support. We evaluate the effect of screw placement and articular subsidence with this fracture pattern. Methods: A retrospective cohort study of operatively treated tibial‐plateau fractures with free osteochondral fragments was performed to determine if screw placement was correlated with articular subsidence. Primary outcome was the relationship between screw to joint distance and articular subsidence. Secondary outcomes were whether bicortical fixation, presence of bone graft, fracture characteristics and patient age was correlated with articular subsidence. Results: Sixty‐eight of 309 tibial‐plateau fractures had depressed osteochondral fragments (22%). The average thickness of these fragments was 10.2 mm. Fractures with raft screws placed closer to the joint than the thickness of the osteochondral fragment were less likely to subside (1.8 versus 3.4 mm; P  = 0.02). The proportion of fractures with no radiographic subsidence was also greater in this cohort versus fractures with distal screw placement (33% versus 8%; P  = 0.02). Articular comminution ( P  = 0.04) and female patients aged over 65 years ( P  = 0.03) were associated with increased articular subsidence. Conclusion: Fractures fixed with screws closer to the joint than the thickness of the osteochondral fragment were correlated with less articular subsidence. The 'screw‐joint distance' may help guide screw placement intra‐operatively. Abstract : In the operative fixation of tibial‐plateau fractures with displaced osteochondral fragments, decreased screw to joint distance is associated with decreased articular subsidence at time of union. The screw to joint distance is a simple measure which may help guide intra‐operative screw placement.